Social support, gender and pill burden influence viral load suppression among HIV-infected adolescents and young adults in rural south-western Uganda - Brown, Whitney Elena; Malagala, Hakim; Bajunirwe, Francis (Vulnerable Children and Youth Studies, 2021)
Adolescents and young adults (AYA) carry a significantly higher risk for HIV infection compared to the general population. HIV-infected AYA also have poorer adherence and viral load (VL) suppression compared to older adult patients. Social support may provide an avenue for interventions to improve adherence and VL suppression in this population. We conducted a cross-sectional study in rural southwestern Uganda to examine the association between social support and VL suppression. We measured family cohesion and various sources of social support namely parent/guardian, teachers, classmates and friend using validated scales, and reliability of the scales using Cronbach’s alpha was at least 0.70 on all of them. We defined VL suppression as having less than 1000 copies per ml. We used logistic regression analysis to calculate odds ratios (OR) for the association and to adjust for potential confounders. We enrolled 255 AYA, age range 12–24 years and 50.6% of them were male. Viral load suppression was present in 72.9% of them. In the multiple regression analysis, friend social support was associated with a 10% increase in the odds of VL suppression for every unit increase on the social support scale (OR = 1.10 95% CI 1.05, 1.14). Waiting for more than 15 minutes to see the doctor at the clinic was associated with an almost 2.5-fold increase in the odds of VL suppression (OR = 2.46, 95% CI (1.23–4.92). Males had 48% lower odds of having VL suppression (OR = 0.52, 95% Cl, 0.27–0.98) compared to females. Experiencing side effects on antiretroviral therapy (OR = 0.46 95% CI 0.22–0.95), and taking two or more pills per dose (OR = 0.21 95% CI 0.06–0.75) were associated with lower odds of VL suppression. In conclusion, social support is positively associated with VL suppression, and interventions to enhance social support should be developed and tested among HIV-infected AYA.
Keywords: Adolescents; HIV; Social support; Viral load suppression